HUBUNGAN KURANG ENERGI KRONIK DAN ANEMIA PADA IBU HAMIL DENGAN STATUS GIZI BAYI USIA 6-12 BULAN DI KABUPATEN BOYOLALI (CORRELATION CHRONIC ENERGY DEFICIENCY AND ANEMIA DURING PREGNANCY WITH NUTRITIONAL STATUS OF INFANT 6 – 12 MONTHS IN BOYOLALI REGENCY) - Yunilla Prabandari; Diffah Hanim; Risya Cilmiaty AR; Dono Indarto (Persagi, 2016)
ABSTRACTMalnutrition still becomes a problem in developing countries such as Indonesia. In Boyolali regency the prevalence of stunting and wasting of infants was 27,5 percent and 6,6 percent respectively. The aim of this study was to analyze the correlation between chronic energy deficiency and Anemia on pregnant mothers with the nutritional status of infants aged 6-12 months. Prospective cohort design was implemented in authorized administration of 6 Community Health Centers of Boyolali Regency. A number of 40 pregnant mothers who had record of chronic energy deficiency and Anemia during third trimester and have infants aged 6-12 months participated in the study. Statistic analyzed were performed using the Peason’s Correlation method. The study failed to show the relationship between chronic energy deficiency during pregnancy and z-score of weight for age (WAZ), height for age (HAZ) and weight for height (WHZ) of infants p>0.05 while anemic pregnant mother found a correlation with Z-score of weight for height (WHZ) of infants (p<0.05), but had not correlation with z-score of weight for age (WAZ), height for age (HAZ) (p>0.05) of infant 6-12 months. Thus, early improvement nutrition program for adolescence should be done to prevent malnutrition in pregnant mothers such as chronic energy deficiency and anemia.ABSTRAK Gangguan gizi masih merupakan masalah di negara berkembang termasuk Indonesia. Di Kabupaten Boyolali prevalensi balita pendek (stunting) sebesar 27,5 persen dan kurus (wasting) 6,6 persen. Penelitian ini bertujuan menganalisis hubungan riwayat kurang energi kronik (KEK) dan anemia pada ibu hamil dengan status gizi bayi usia 6-12 bulan. Desain Penelitian adalah kohort prospektif di enam wilayah Puskesmas, di Kabupaten Boyolali. Partisipan terdiri dari 40 ibu yang memiliki riwayat KEK dan anemia pada kehamilan trimester III, memiliki bayi berusia 6-12 bulan. Analisis statistik menggunakan uji korelasi pearson. Pada penelitian ini tidak ditemukan hubungan riwayat KEK pada ibu hamil dengan status gizi bayi usia 6-12 bulan (Indeks BB/U, PB/U dan BB/PB) (p>0,05). Riwayat anemia pada ibu hamil berhubungan dengan status gizi bayi indeks BB/PB (p<0,05), akan tetapi tidak berhubungan dengan status gizi indeks BB/U dan PB/U (p>0,05). Perbaikan pencegahan kurang gizi dan anemia pada masa remaja atau calon pengantin diperlukan untuk mencegah terjadinya gizi kurang pada ibu hamil dan generasi selanjutnya.